Utilization of Social Media as Indonesia's Tourism Public Relations Strategy - Tania Rizqia Putri; Firman Kurniawan Sujono (International Journal of Social Service and Research, 2023)
Tourism is one of the main economical sectors in Indonesia, supported by enormous tourism potential of existing tourist destinations and cultural diversity. Various modes of promotions are required in order to further raise tourists’ awareness of existing tourist destinations and to build a positive tourism image of Indonesia. The use of social media is one of the most effective solution in promoting Indonesian tourism, that is also in line with the digitalization in public relations 4.0 development. Using the Systematic Literature Review method of five journals from Google Scholar in the last four years, it was found that Instagram is the most widely used social media to promote tourism in Indonesia.